Negotiating ethnic conflict in Sri Lanka: An analysis of failure of political solutions (Note) - Watts, Edward; Slater, Richard (1999)
Analysing failure of 1994-95 peace talks to resolve Shri Lankan ethnic crisis, the authors examine in detail the rationales, motives and commitment of actors (Sri Lankan Government and LTTE) involved in the peace process; complex and interlocking sets of constraints; difficulties in reaching a satisfactory devolution agreement; and both sides unrelentingly nurturing their commitment to gain strategic advantage. The authors argue in the concluding section the need to uphold people's need for peace with a caution that persistence of both sides in not conceding strategic ground is bound to result in prolonging an unwinable war or revertion to open warfare. - Reproduced
Keywords: Note; Ethnic conflicts - Sri Lanka; Ethnic conflicts